Compartmentalization of sodium in the human brain: a mini-review of 23Na-MRI methods - Egidi, Irene; Guidi, Maria; Giove, Federico (Frontiers in Physics, 2025)
Sodium magnetic resonance imaging is a non-invasive technique that provides information about sodium levels in tissues. It has significant applications in brain research due to the important role of sodium in both normal brain function and pathological processes. Total sodium concentration is the most widely used derived metric; it offers insights into sodium content across different brain regions. However, the functional role of sodium is closely linked to its distribution within intra- and extracellular spaces. Sodium osmotic homeostasis affects the intracellular volume fraction, a parameter that can be altered in various neurological disorders. Unfortunately, distinguishing intracellular from extracellular sodium nuclear magnetic resonance signals is challenging, even with the use of contrast agents. In recent years, several methodologies have been proposed to study sodium compartmentalization in humans, typically involving tailored acquisition techniques and modeling approaches. This mini-review provides a brief overview of the challenges, methodologies, and potential applications of compartmentalized sodium MR imaging in human neuroscience.